MODELOS NÃO LINEARES APLICADOS PARA CLASSIFICAÇÃO DE SÍTIOS FLORESTAIS DE Pinus Elliottii E pinus taeda - FIORENTIN, Luan Demarco; MIRANDA, Rodrigo Otávio Veiga de; ARCE, Julio Eduardo; FIGUEIREDO FILHO, Afonso; TÉO, Saulo Jorge; HOINACKI, Reinaldo da Costa (Brazilian Journal of Biometrics, 2017)
The objectives of this research were to test statistical models to classify the sites of the Pinus elliottii and Pinus taeda stands, at Caçador region, Santa Catarina, Brazil, and to propose the use of the lack of fit test to evaluate the anamorphism of the site index curves. Site classification was performed by guide-curve method, for reference age of 25 years, and four nonlinear regression models were tested. The relation between dominant height and site index were evaluated by anamorphism test and lack of fit test. The models tested showed similar performance for dominant height estimates, except for Clutter and Jones model. The Bailey of 4 Parameters model showed superior fitting and precision statistics for Pinus elliottii and Pinus taeda and it was used to generate the index sites curves for both species. The anamorphism test and lack of fit test indicated anamorphic pattern for site index curves for Pinus elliottii and Pinus taeda species. The lack of fit test was appropriate to evaluate the anamorphism of the site index curves.